PENGUKURAN TINGKAT KEBISINGAN PESAWAT CASA 212-200 SAAT GROUND RUN TEST BERDASARKAN VARIASI SUDUT - Adam Wahyu Saputra Adam; Mufti Arifin; Ericko Chandra Utama (FTK UNSURYA, 2023)
Noise is an unwanted sound, including sound that as a result of side effects from activities such as industrial and transportation activities. The greatest intensity of noise in the aircraft maintenance hangar environment is produced by the operation of the aircraft engine when it is ground or what is often called the Aircraft Ground Run Test. An This study was conducted by taking samples using CASA 212-200 aircraft equipped with a turboprop engine type. The measurement of noise generated by aircraft activity is measured using a tool such as the AS804 Sound Level Meter. This study aims to determine the intensity of aircraft noise when conducting a ground run test which is measured based on variations in the angle of measurement location to the source with a distance of 30 m based on an angular reference of 0o in front of the aircraft nose and 180o is behind the aircraft with a clockwise rotation. The measurement of noise levels is based on three references, namely LAmax, LAmin and LAeq. At idle the variation in the direction of the noise receiver which has the potential to produce the largest LAmax value at an angle (30o) of 97 dB. The lowest LAmin at an angle (180o) and (210o) of 84.6 dB. The largest LAeq at an angle (330o) of 95.3 dB. At the time of max power the variation in the direction of the noise receiver which has the largest potential LAmax value at an angle (45o) of 99.1 dB, the lowest LAmin at an angle (135o) of 94.8 dB. The highest LAeq at an angle (45o) of 97.8 dB.